Encyclopedia of geropsychology - Pachana, Nancy A. (Springer, 2016)
This encyclopedia brings together key established and emerging research findings in geropsychology. It is a comprehensive coverage of the entire breadth of the field, giving readers access to all major subareas and illustrating their interconnections with other disciplines. Entries delve deep into key areas of geropsychology such as perception, cognition, clinical, organizational, health, social, experimental and neuropsychology. In addition to that, the encyclopedia covers related disciplines such as neuroscience, social science, population health, public policy issues pertaining to retirement, epidemiology and demography, and medicine. Paying careful attention to research internationally, it cites English and non-English empirical literature from around the globe. This encyclopedia is relevant to a wide audience that include researchers, clinicians, students, policy makers and nongovernmental agencies
Gesehen am 19.04.2016